Studentsâ Ability in Using Discourse Markers to Build Coherence in Compositions - Prastiyowati, Santi (Journal of English Language, Literature, and Teaching (J-ELLiT), 2017)
This study describes the difficulties in listening comprehension encountered by first-year students of English Department. This study employs descriptive qualitative method. Questionnaires with close and open-ended questions are used as the research instrument. The subject of this study was 42 students of English Department who had completed their first semester. The study revealed that several problems occurred in the teaching and learning of listening. The problems were related to listenersâ performance, listening materials, studentsâ physical limits, and supporting equipment. Based on the data obtained, the major problems faced by the students were related to listening materials and studentsâ performance. Different phonological system, which was related to the materials, and guessing unknown words seemed to affect their listening comprehension. The study also found that the students applied several strategies to develop their listening mastery. Most of them (78.6%) conducted independent study outside the class. Most of them prefer listening to English songs and watching English movies. Some loved to listen to news and watching YouTube videos.